Análisis de factibilidad para la implementación de un software de sistema de gestión para el Crossfit Mañungofit. - Hostacio Espinoza, Yinihor Johao (2025)
The following case study entitled “Feasibility analysis for the implementation of a management system software for CrossFit Mañungofit” is based on the feasibility of deploying a platform for the management of interactions with clients, through a management system for CrossFit Mañungofit in the city of Babahoyo. The main objective is to determine the feasibility of implementing a management system software for CrossFit Mañungofit. To achieve this, surveys were conducted with 2 trainers belonging to there and 100 members who will train in three different shifts: morning, afternoon and night. This study has extensive research as its objective to analyze the feasibility of implementing a management system software for CrossFit Mañungofit, with the result of optimizing its administrative processes and improving the experience of those who attend. CrossFit has been facing certain difficulties in information management, class scheduling, user monitoring, among others, which affects its operational efficiency. To address these issues, different management systems available will be analysed, assessing their technical, economic and operational viability. In addition, this research will propose software that meets the specific needs of CrossFit Mañungofit, in order to improve internal organisation and offer a better service to all users. This study therefore aims to determine how the implementation of a management system can contribute to the growth and sustainability of CrossFit, optimising resources and increasing member satisfaction.